The power of God : a Jonathan Edwards commentary on the book of Romans - Edwards, Jonathan, 1703-1758; Lovi, David S.; Westerhoff, Benjamin (Cambridge : The Lutterworth Press, 2013)
Paul's epistle to the Romans is one of the most beloved writings in the entire biblical canon, especially for Augustinians and Protestants. It is the subject of thousands of commentaries, many by the most important doctors of the church: Augustine, Aquinas, Luther, Calvin, Hodge, and Barth, to name a few. It offers the doctrines of sin, the gospel, and salvation in a nutshell. It is the basis for the structure of the first Protestant textbook in what later came to be categorized as systematic theology, Philip Melanchthon's Loci Communes (1521). It is a frequently-cited sourcebook of the Reform.
Front Cover; Title Page; Copyright; Contents; Dedications; Foreword; Introduction; ROMANS CHAPTER 1; ROMANS CHAPTER 2; ROMANS CHAPTER 3; ROMANS CHAPTER 4; ROMANS CHAPTER 5; ROMANS CHAPTER 6; ROMANS CHAPTER 7; ROMANS CHAPTER 8; ROMANS CHAPTER 9; ROMANS CHAPTER 10; ROMANS CHAPTER 11; ROMANS CHAPTER 12; ROMANS CHAPTER 13; ROMANS CHAPTER 14; ROMANS CHAPTER 15; ROMANS CHAPTER 16; Jonathan Edwards' Romans Sermon Explications; Back cover.
Includes index.
Print version record.
Master record variable field(s) change: 072
Keywords: Bible. -- Commentaries; Bible; RELIGION -- Biblical Studies -- New Testament; RELIGION -- Biblical Studies -- Paul's Letters; RELIGION / Biblical Studies / Paul's Letters; Electronic books; Commentaries